The Oncogenic Role of miR-21 in Cancer Progression: A Molecular Review - Farman Ullah; Shakeel, Faiqa; Muhammad Ilyas; Noor, Amna; Nazar, Mobara; Fatima, Wajiha; Noreen, Zarish; Moeez, Sadaf (Indus Journal of Bioscience Research, 2025)
Small non-coding RNAs known as microRNAs (miRNAs) are essential for controlling genes, and miR-21 has been shown to be a strong carcinogen in a variety of malignancies. The mechanisms of miR-21 are described in detail in this review, including the suppression of tumor suppressors like PTEN and PDCD4, the activation of pathways like PI3K/AKT, and the encouragement of aggressive phenotypes like invasion, proliferation, and resistance to treatment. Through exosomal transfer, miR-21 modifies the tumor microenvironment (TME), promoting stromal remodeling and immune suppression. Its potential as a diagnostic and prognostic biomarker is highlighted by its detectability in circulation and consistent upregulation in cancers. Anti-miR oligonucleotides and nanoparticle delivery are two therapeutic approaches that exhibit preclinical promise but struggle with specificity and clinical translation. The functions of miR-21 are summarized in this review, with a focus on novel delivery methods and standardized assays as the means of achieving its full therapeutic potential.